The Effectiveness of Visual Media in Enhancing Arabic Vocabulary Mastery - Alfah, Devi Afniatus Zulinda; Ma'arif, M. Syamsl; Muslimah, Maziyyatul (Al-Wazan: Journal of Arabic Education, 2025)
This study investigates the effectiveness of using visual media in enhancing students’ mastery of Arabic vocabulary among tenth-grade students at MA Abdul Hadi Ngudirejo Jombang. The research addresses the problem of limited vocabulary acquisition and low student engagement in Arabic language learning when conventional teaching methods are applied. The study aims to determine whether image-based media can significantly improve students’ vocabulary mastery compared to traditional instruction. The research employed an experimental method using a Non-Equivalent Pretest–Posttest Control Group Design. Two groups were selected through cluster random sampling: one experimental class and one control class, each consisting of twelve students. The experimental class was taught using image media, while the control class followed conventional learning. Data were collected through pretests and posttests to measure the improvement in vocabulary mastery. The results revealed that students in the experimental class achieved significantly higher posttest scores than those in the control class, demonstrating that the use of visual media effectively enhanced vocabulary learning. The findings suggest that incorporating image-based learning tools can foster greater engagement, retention, and comprehension in Arabic vocabulary instruction. This study contributes to the development of more interactive and effective pedagogical approaches for Arabic language teaching in secondary education